Level Up! Making Games Accessible - Brunk, Angie; Monobe, Dale (Chicago, Illinois : Association of College and Research Libraries, 2020)
Games are firmly established as a tool in the librarian’s toolbox. Gamification of instruction allows librarians to reach more students in instruction both online and in person by creating more engaging library instruction sessions or online tutorials. Library game nights and other programming that includes games allow us to draw more students into the library. Unfortunately, instructional and outreach activities that are not designed with accessibility and inclusivity in mind from the beginning can make students with disabilities feel unwelcome in the library. In this chapter, we will cover some of the foundational aspects of accessible gamification. We will also detail how to prepare for potential accessibility pitfalls and suggest possible remedies.